The Dark Side of the Force: Evolutionary Equilibrium in Contests with Stochastic Entry - Yiquan Gu; Burkhard Hehenkamp; Wolfgang Leininger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We study evolutionarily stable strategy (ESS) in contests where participation is stochastic. When participation probabilities are given, players exert more effort In ESS than under Nash. Ex-ante overdissipation occurs when participation is suff. likely and discriminative power of the contest suff. high. When entry is costly and endogenous, players' entry is more likely, more costly, and less profitable in ESS than under Nash. Ex-ante overdissipation also occurs for concave impact functions.
Keywords: D72; C73; 330